2012
DOI: 10.1016/j.mce.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog signaling during adrenal development

Abstract: It has been speculated for a number of years that Sonic hedgehog (Shh) signaling plays an important role in adrenal development. Over the past two years several reports have described the expression and function of Shh pathway genes in the adrenal cortex, using primarily mouse models. The key findings are that Shh signals produced by a population of partially differentiated cortical cells located in the outer cortex/zona glomerulosa are received by non-cortical mesenchymal cells located predominantly in the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 75 publications
0
51
0
1
Order By: Relevance
“…The fetal zone regresses after puberty in mice while the definitive cortex subdivides in a thin outer zona glomerulosa synthesizing mineralocorticoids and a thick inner zona fasciculata producing glucocorticoids. Homeostasis of the adrenal cortex is mediated by capsular and subcapsular progenitors that give rise to steroidogenic cells that move centripetally (for reviews see Laufer et al, 2012;Walczak and Hammer, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The fetal zone regresses after puberty in mice while the definitive cortex subdivides in a thin outer zona glomerulosa synthesizing mineralocorticoids and a thick inner zona fasciculata producing glucocorticoids. Homeostasis of the adrenal cortex is mediated by capsular and subcapsular progenitors that give rise to steroidogenic cells that move centripetally (for reviews see Laufer et al, 2012;Walczak and Hammer, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…11 Moreover, in the testis, studies have demonstrated that Sf-1 is also produced by the Sertoli and Leydig cells. 8 Sf-1 has been shown to regulate the synthesis and secretion of steroid hormone (androgen) through directing the expression of steroidogenic enzymes, such as steroidogenic acute regulatory cytochrome P450, to produce testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…LOH, rearrangements and abnormal imprinting of the 11p15.5 locus, resulting in increased IGF2 expression and decreased p57kip2 and H19 expression, have frequently been found in sporadic ACTs [143][144][145].…”
Section: Igf Signaling Pathwaymentioning
confidence: 99%
“…IGF2 mRNA expression is increased in 8.5 and 90% of adult ACAs and ACCs, respectively. In adult patients, but not in pediatric patients, IGF2 overexpression was associated with unfavorable outcome and increased recurrence risk [5,15,[144][145][146].…”
Section: Igf Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation